Profitability Ratio Analysis to Measure Financial Performance - Melinda Handayani; Muhammad Iqbal; Erwin Budianto; Nurhana Dhea Pharlina (LPPM of NAROTAMA UNIVERSITY, 2026)
Purpose: This research aims to evaluate the profitability ratios of companies in the Food and Beverage sector listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. The study specifically focuses on analyzing the Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and Gross Profit Margin (GPM) as key indicators of financial performance. Design/methodology/approach: The study employs a quantitative analysis using financial data from annual reports of publicly listed Food and Beverage companies. Profitability ratios are calculated for each company over the four-year period and analyzed for trends and fluctuations. Statistical tools are used to assess the relationship between profitability ratios and factors such as operational efficiency, asset management, and market conditions. Findings: The findings indicate significant fluctuations in profitability ratios, reflecting challenges in cost management, asset utilization, and market competition. The study reveals that while some companies successfully managed to improve their profitability, others faced difficulties due to rising operational costs and inefficiencies in asset utilization. The analysis highlights the importance of controlling production costs, optimizing asset management, and adjusting pricing strategies to improve profitability. Paper type: Research Paper